GPER mediates decreased chemosensitivity via regulation of ABCG2 expression and localization in tamoxifen-resistant breast cancer cells. (15th April 2020) - Yu, Tenghua; Cheng, Hong; Ding, Zhijuan; Wang, Zhiliang; Zhou, Lixia; Zhao, Peng; Tan, Shengxing; Xu, Xue; Huang, Xianming; Liu, Manran; Peng, Meixi; Qiu, Yu-an
Abstract: Rescue chemotherapy is usually the preferred treatment for patients with advanced estrogen receptor-positive (ER+) breast cancer with endocrinotherapy resistance. However, these patients often simultaneously show a poor response to cytotoxic drugs, and thus the detailed mechanism of this resistance needs to be further investigated. Our previous research indicated that the G-protein-coupled estrogen receptor (GPER) is a novel mediator of the development of multidrug resistance, including resistance to both endocrinotherapy and chemotherapy, and ATP binding cassette subfamily G member 2 (ABCG2) has been identified as an engine that confers cancer cells with chemoresistance by expelling xenobiotics and chemotherapeutics. Here, we are the first to show that the expression levels of GPER and ABCG2 are markedly increased in tamoxifen-resistant ER + metastases compared to the corresponding primary tumors. A plasma membrane expression pattern of GPER and ABCG2 was observed in patients with metastases. Furthermore, both ER modulator tamoxifen, GPER-specific agonist G1 and pure ER antagonist ICI 182, 780 significantly enhanced ABCG2 expression in tamoxifen-resistant breast cancer cells (MCF-7R) but not in tamoxifen-sensitive cells (MCF-7). The activated downstream GPER/EGFR/ERK and GPER/EGFR/AKT signaling pathways were responsible for regulating the expression and cell membrane localization of ABCG2, respectively, in MCF-7R cells. Interestingly, the above phenomenon could be alleviated by inhibitors of both the indicated signaling pathways and by knockdown of GPER in MCF-7R cells. More importantly, the tamoxifen-induced GPER/ABCG2 signaling axis was shown to play a pivotal role in the development of chemotherapy (doxorubicin) resistance both in vitro and in vivo. The clinical data further revealed that tamoxifen-resistant patients with high GPER/ABCG2 signaling activation had poor progression-free survival (PFS) when given rescue anthracycline chemotherapy. Therefore, our data provide novel insights into GPER-mediated chemoresistance and provide a rationale for the GPER/ABCG2 signaling axis being a promising target for reversing chemoresistance in patients with advanced ER + tamoxifen-resistant breast cancer. Highlights: GPER and ABCG2 expression are positively correlated in TAM-resistant breast cancer. GPER signals regulate ABCG2 expression and localization of TAM-resistant cancer cells. GPER/ABCG2 axis confers the resistance to chemotherapy in TAM-resistant breast cancer. GPER/ABCG2 axis is an alternative target to reverse chemoresistance in breast cancer.